2021
DOI: 10.3389/fphar.2021.705405
|View full text |Cite
|
Sign up to set email alerts
|

Brimonidine is Neuroprotective in Animal Paradigm of Retinal Ganglion Cell Damage

Abstract: To investigate the neuroprotective effect of brimonidine after retinal ischemia damage on mouse eye. Glaucoma is an optic neuropathy characterized by retinal ganglion cells (RGCs) death, irreversible peripheral and central visual field loss, and high intraocular pressure. Ischemia reperfusion (I/R) injury model was used in C57BL/6J mice to mimic conditions of glaucomatous neurodegeneration. Mouse eyes were treated topically with brimonidine and pattern electroretinogram were used to assess the retinal ganglion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 41 publications
0
31
0
2
Order By: Relevance
“…Several strategies have been explored to slow down the loss of RGCS following several types of retinal insults, including the use of alpha two agonists [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] and the use of substances with neuroprotective properties, such as trophic factors and neurotrophins [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], of which BDNF is the most potent neuroprotectant for the retina [ 30 ], and the caspase inhibitors [ 31 ], among others [ 32 ]. Moreover, different pharmacological approaches have provided new evidence of RGCs protection [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies have been explored to slow down the loss of RGCS following several types of retinal insults, including the use of alpha two agonists [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] and the use of substances with neuroprotective properties, such as trophic factors and neurotrophins [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], of which BDNF is the most potent neuroprotectant for the retina [ 30 ], and the caspase inhibitors [ 31 ], among others [ 32 ]. Moreover, different pharmacological approaches have provided new evidence of RGCs protection [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous studies have found a potential pro-inflammatory effect on the retina of topically applied benzalkonium chloride, a preservative commonly used in eye-drops [29]. Moreover, α2-adrenergic agents are known to exert a neuroprotective effect on RGCs in vitro [30,31], in animal models of glaucoma [32,33] and potentially in human subjects affected with normal tension glaucoma [34]. However, the aim of this pilot study was uniquely to investigate the numerosity of HRS in patients affected with glaucoma in comparison to healthy controls, and is underpowered to find differences among patients treated with different topical hypotensive agents.…”
Section: Discussionmentioning
confidence: 99%
“…Newer drugs including a conjugate of latanoprost and an NO-donor (latanoprostene bunod, approved 2017; Cavet et al, 2014) Kirihara et al, 2018a;Kirihara et al, 2018b;Fuwa et al, 2018;Fuwa et al, 2021;Ferro Desideri et al, 2019;Aihara et al, 2020a;Aihara et al, 2020b;Sharif et al, 2020) (Figure 9). Interestingly, some drugs like brimonidine and betaxolol, not only lower IOP but are also neuroprotective, at least in animal models of IOPdependent and IOP-independent glaucomatous damage (e.g., Rusciano et al, 2017;Conti et al, 2021).…”
Section: Pharmaceutical and Cellular Therapeutics To Lower Intraocular Pressurementioning
confidence: 99%
“…Of the drugs that have been clinically evaluated for neuroprotective activity and to retard vision loss or impairment in POAG patients, for example brimonidine and memantine, none have conclusively proven effective thus far (Almasieh and Levin, 2017;Levin, 2017). It is worth noting that a very recent study demonstrated the neuroprotective activity of brimonidine after retinal ischemia (Conti et al, 2021). There is some hope and promise that oral vitamin-B3/ nicotinamide may offord some degree of functional vision preservation in POAG patients (Williams et al, 2017c;Hui et al, 2020).…”
Section: Need For Neuroprotection In Glaucoma Treatmentmentioning
confidence: 99%